"Ty kan man sin egen historia, blir det lättare att kämpa för sin egen identitet". : En kvalitativ analys av ett samiskt perspektiv på utbildningspolitik mellan 1962-1994. - Appelblad, Julia (Umeå universitet, Institutionen för idé- och samhällsstudier, 2016)
This thesis intends to examine a sámi perspective on Swedish educational policy between 1962 and 1994. To do so the curriculum of the Swedish schools and the sámi schools are analyzed. The sámi perspective in the thesis is represented by the debate about educational policy in a sámi journal, Samefolket.The results show that the Swedish curriculums from 1962-1994 don’t mention the sámi people and only the last one, the one from 1980, are stating shortly that groups within Sweden are to be treated with solidarity. Otherwise the sámis aren’t mentioned. In the curriculums for the sámi schools that only permitted sámi children, one can find that the purpose of those schools were to strengthen the sámi people in their culture and language.In the debate about education politics in the journal Samefolket it appears that there were three themes of subjects that were central in the debate. The first was the debate on the organizational form of the sámi schools. It appears that the voices in the debate of educational policy in Samefolket wanted greater sami influence in the sami school, however, this study shows that the Samefolket-debate did not comment on the educational policy reforms themselves. The study shows that the sámi voices in Samefolket wanted to keep the special sámi schools and that the two motives, which was the second theme of the debate, were to keep and to defend their culture. In the curriculum för the sami schools, this was also the motive. The third theme was of how the school system in Sweden was educating the non-sámi people about the sámi. In this theme the prime focus was about how sámis were represented in Swedish textbooks and the study shows that there were, according to the voices in Samefolket, a great disappointment in these.At last, from a culture imperialistic theory one can make the observation that the sámi schools were motivated as an important institution because the Swedish school system couldn’t give the sámi an education to fulfill their cultural needs. This ...